Theorem on integral inequalities with functional argument - Musaev, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A theorem on the integral Volterra-Fredholm inequalities with a functional limit is proved. By using this theorem, the theorem on integral inequalities with retarded argument is established.